2023
DOI: 10.1039/d3ra02054a
|View full text |Cite
|
Sign up to set email alerts
|

A green and efficient two-step enzymatic esterification-hydrolysis method for enrichment of c9,t11-CLA isomer based on a three-liquid-phase system

Zhigang Li,
Yinglin Fang,
Jiawei Yang
et al.

Abstract: A novel two-step enzymatic esterification-hydrolysis method that generates high-purity conjugated linoleic acid (CLA) isomers was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Enzymatic approaches are more highly efficient and specific than traditional chemical processes. 23–26 Many works had been reported on the biocatalysis of purine nucleoside esters. The lipase from C. antarctica was used to catalyze 5′-O-acylated adenosines by V. Gotor et al 27 In this work, the target products were obtained in DMSO for 18–24 h. Zhao et al reported that regioselective acylation of cytarabine catalyzed by Pseudomonas fluorescens whole-cells was obtained after 144 h. 28 Regioselective undecylenoylation of adenosine catalyzed by Candida antarctica lipase B needed 23 h. 29 These works are of great significance for the biocatalysis of purine nucleoside esters.…”
Section: Introductionmentioning
confidence: 99%
“…Enzymatic approaches are more highly efficient and specific than traditional chemical processes. 23–26 Many works had been reported on the biocatalysis of purine nucleoside esters. The lipase from C. antarctica was used to catalyze 5′-O-acylated adenosines by V. Gotor et al 27 In this work, the target products were obtained in DMSO for 18–24 h. Zhao et al reported that regioselective acylation of cytarabine catalyzed by Pseudomonas fluorescens whole-cells was obtained after 144 h. 28 Regioselective undecylenoylation of adenosine catalyzed by Candida antarctica lipase B needed 23 h. 29 These works are of great significance for the biocatalysis of purine nucleoside esters.…”
Section: Introductionmentioning
confidence: 99%